Re-Emergence of Ampicillin Sensitive Salmonella Typhi and the Increase of Ciprofloxacin Resistance in Typhoid Fever Treatment in Asia: A Systematic Review - Tanjaya, Felicity; Nathan, Johan; Nainggolan, Ita Margaretha; Moehario, Lucky; Thantry, Anita Devi Krishnan; Tunru, Andi Miyanza Lakipadada; Sean, Sherlyn (Indonesian Journal of Tropical and Infectious Disease, 2024)
Typhoid fever is a disease caused by Salmonella Typhi infection. In 2000, 2.16 million people were affected worldwide, with more than 90% morbidity and mortality in Asia. Ampicillin is the first-line antibiotic used for typhoid management. However, the rise in resistance to first-line antibiotics has shifted ciprofloxacin as an alternative.  This study aimed to describe the trends in ciprofloxacin- and ampicillin-resistant Salmonella Typhi in Asia. This study was a systematic review that conformed to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria. Search was indicated toward studies on Salmonella Typhi susceptibility toward ciprofloxacin and ampicillin were identified using PubMed, Cochrane Library, and ProQuest. Of the 1542 studies found, only 16 fulfilled the criteria. In 1996, Salmonella Typhi was not found to be resistant to ciprofloxacin, whereas 3.5% was resistant to ampicillin. In 2005, ciprofloxacin resistance increased to 19.3%, whereas ampicillin resistance decreased to 13.3%. In 2005-2014, a larger number of Salmonella Typhi isolates resistant to ciprofloxacin than to ampicillin. Furthermore, during 2016-2019, resistance to ciprofloxacin increased from 8.1% to 95%, while ampicillin resistance increased from 27.5% to 85.2%. This the high ampicillin resistance in South and East Asia. In Asia, there was an increase in ciprofloxacin-resistant Salmonella typhi from 1996 to 2019, whereas ampicillin-resistant Salmonella Typhi decreased from 1996 to 2015.  Between 2016 and 2019, contrasting evidence was found in East Asia and South Asia, where resistance toward ampicillin increased.